Gingival Changes after Immunosuppressive Therapy II. - A. Fassmann; P. Augustín; J. Slapnička (Czech Dental Chamber, 2005)
There are emerging new problems associated with medication side effect with development of therapeutic modalities of current medical approaches. Some of these, such as Cyclosporin A (CsA), anticonvulsants, calcium channel blockers are associated with gingival overgrowth. We know the pharmacological mechanism of action, clinical and histopathological pictures, but the question about etiopathogenesis remains still open. The mechanism of gingival hyperplasia development is complicated and includes action of many co-factors, such as plaque, genetic predisposition, age and hormones. Drug-induced gingival overgrowth appears to be more prevalentin children and adolescents and has a predilection for the anterior gingival tissues. Gingival changes can occur within 3 month of dosage. The pattern of overgrowth development shows intra-patient variation, but may reach a "state of equilibrium" often within the first year of commencing medication. Changes in drug therapy or systemic illness may alter this state and lead to further gingival changes. Most studies show that an association therapy or systemic illness may alter this state and lead to further gingival changes. Most studies show an association between oral hygiene status and both the prevalence and severity of drug-induced gingival overgrowth. The question is whether the plaque is the contributory factor or a consequence of the gingival changes.